2018
DOI: 10.1177/0825859718759881
|View full text |Cite
|
Sign up to set email alerts
|

The Doctor–Patient Relationship and Information-Seeking Behavior

Abstract: Participants exhibited different information-seeking behaviors based on how they interpreted the role of their physician as information giver. This affected what kind of information they sought and how they understood the information received, which in turn affected understanding of their broader experience and care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 39 publications
(69 reference statements)
1
40
0
Order By: Relevance
“…Round boxes represent individual doctors, red represents individuals with core attributes, and gray represents individuals with edge attributes. Among them, some doctors (individuals 1, 2, 3, 8, 10,12,31,34,35,36,39,40,42,44,47,53,56,61,62,66,68,69,73,84,86,87,92,96,100,102) are in the core area. According to the calculation results, the core area network density in the network is 0.455, and the periphery area network density is 0.181.…”
Section: Node Freeman's Degree Freeman's Betweenness Closenessmentioning
confidence: 99%
See 3 more Smart Citations
“…Round boxes represent individual doctors, red represents individuals with core attributes, and gray represents individuals with edge attributes. Among them, some doctors (individuals 1, 2, 3, 8, 10,12,31,34,35,36,39,40,42,44,47,53,56,61,62,66,68,69,73,84,86,87,92,96,100,102) are in the core area. According to the calculation results, the core area network density in the network is 0.455, and the periphery area network density is 0.181.…”
Section: Node Freeman's Degree Freeman's Betweenness Closenessmentioning
confidence: 99%
“…Additional indicators are needed for verification. By comparing effective size, efficiency, and constraint, it can be found that individuals 1,18,35,40,42, and 102 are located in the structural hole of the network (i.e., the middleman of the network), and the degree of reciprocity is high. Doctors in such nodes can connect to two areas, or they can bring location benefits through a reciprocal relationship with the structural hole location (Figure 3).…”
Section: Reciprocal Exchangementioning
confidence: 99%
See 2 more Smart Citations
“…Although it is now common for US adults to search online for health information, patients can have different approaches to information-seeking and communicating about health information with their health care team. A study of cancer patients classified these different information-seeking orientations into 4 categories: the "questioners" who often distrust physician-provided information; the "undecided" who need time to process information and make decisions; the "cross-checkers" who prefer to double check information they receive; and the "experienceoriented" who prefer information from other health consumers over that from providers or research [19]. While these categories may not be generalizable to all types of patients, knowing that patients can approach information-seeking in different ways and that a patient's information-seeking behavior is related to their view of the physician as "information-giver" illustrates the importance of strong physician-patient communication [19].…”
Section: Assess Patient Engagement Needsmentioning
confidence: 99%